Optimization of Furniture Raw Material Inventory Using The Lagrange Multiplier Method - Wening, Marshanda Citra; Donoriyanto, Dwi Sukma (AI Society & STMIK Indonesia, 2024)
PT XYZ is a furniture company specializing in products made from wood and rattan. PT XYZ has suboptimal problems controlling raw material inventories, resulting in inventory cost overruns and warehouse overcapacity. This research aims to determine the optimization of the amount of furniture raw material in the inventory according to the available warehouse capacity using the Lagrange Multiplier method. From the research results, it was found that the total warehouse using the Lagrange Multiplier method was 107,922 m3, which shows that this value is optimal because it does not exceed the capacity of the warehouse owned by PT XYZ, which is 108 m3. By applying the Lagrange Multiplier method, it is possible to save total inventory costs of IDR 17.219.173 or 6.36% of the company's total inventory costs, with an order size of 37 m3 for mindi wood and 26 m3 for mahogany wood.